Political Epistemology : Knowledge and Advocacy in Trade Union Research - Edling, Staffan (Lunds universitet, 2024)
Political organisations routinely, and increasingly, employ researchers to make knowledge claims and suggest political action. Swedish blue-collar trade union organisation LO has done so since the 1930s, employing economists and other social scientists drawing in part on methods of analysis and presentation similar to academic social science, and in part on interaction with spokespersons for trade union members to produce texts and other output which they treat as both knowledge-production and advocacy. Starting from assumptions and perspectives from the sociology of science and science and technology studies, I analyse the activities of political researchers in the organisation of LO, drawing on interviews, participant observation and printed documents. Special attention is paid to the interaction between political and epistemic phenomena in their research, and the situational boundaries drawn between the two, from three different angles: in the production of different kinds of linguistic statements, in LO researchers' claims to speak for union members, and in how LO research relates to academia, politics, and other sites as social worlds external to themselves. Through these different analytical angles, I argue that political research at LO involves the interaction between the political representation of union members on the one hand, and the epistemic representation of reality on the other, and occasionally the dissolution of the boundary between the two. As the distinction between speaking for union members and speaking for reality is contextually bound, and at times dissolved, questions of causality between politics and knowledge can only be answered situationally, challenging common assumptions of political research as either value-free or reducible to political strategy.
Keywords: fackförbund; fackliga utredningar; LO; politisk epistemologi; expertis; trade unions; policy research; political epistemology; expertise; LO